The KMOS Cluster Survey (KCS). I. The fundamental plane and the formation ages of cluster galaxies at redshift 1.4 < Z < 1.6 - Beifiori, A; Mendel, J; Chan, J; Saglia, R; Bender, R; Cappellari, M; Davies, R; Galametz, A; Houghton, R; Prichard, L; Smith, R; Stott, J; et al. (American Astronomical Society, 2017)
The American Astronomical Society. All rights reserved. We present the analysis of the fundamental plane (FP) for a sample of 19 massive red-sequence galaxies (M· > ×4 10 10 M·) in three known overdensities at 1.39 1.61 < < z from the K-band Multi-object Spectrograph (KMOS) Cluster Survey, a guaranteed-time program with spectroscopy from the KMOS at the VLT and imaging from the Hubble Space Telescope. As expected, we find that the FP zero-point in B band evolves with redshift, from the value 0.443 of Coma to -0.10±0.09, -0.19±0.05, and -0.29±0.12 for our clusters at z = 1.39, z = 1.46, and z = 1.61, respectively. For the most massive galaxies (log 1 M M· > 1) in our sample, we translate the FP zero-point evolution into a mass-to-light-ratio M/L evolution, finding D log 0.46 0.10 M L z B = - (D log )0.52 0.07 M L z B = -to(D log ) 0.55 0.10 M L z B = - respectively. We assess the potential contribution of the galaxy structural and stellar velocity dispersion evolution to the evolution of the FP zero-point and find it to be ∼6%-35% of the FP zero-point evolution. The rate of M/L evolution is consistent with galaxies evolving passively. Using single stellar population models, we find an average age of 2.33- +0.51 0.86 Gyr for the log 1 M M· > 1 galaxies in our massive and virialized cluster at z = 1.39,1.59- +0.62 1.40 Gyr in a massive but not virialized cluster at z = 1.46, and 1.20- +0.47 1.03 Gyr in a protocluster at z = 1.61. After accounting for the difference in the age of the universe between redshifts, the ages of the galaxies in the three overdensities are consistent within the errors, with possibly a weak suggestion that galaxies in the most evolved structure are older.